Shape effects on the random-packing density of tetrahedral particles - Zhao, Jian; Shuixiang Li; Weiwei Jin; Xuan Zhou (Physical Review E, 2012)
Regular tetrahedra have been demonstrated recently giving high packing density in random configurations. However, it is unknown whether the random-packing density of tetrahedral particles with other shapes can reach an even higher value. A numerical investigation on the random packing of regular and irregular tetrahedral particles is carried out. Shape effects of rounded corner, eccentricity, and height on the packing density of tetrahedral particles are studied. Results show that altering the shape of tetrahedral particles by rounding corners and edges, by altering the height of one vertex, or by lateral displacement of one vertex above its opposite face, all individually have the effect of reducing the random-packing density. In general, the random-packing densities of irregular tetrahedral particles are lower than that of regular tetrahedra. The ideal regular tetrahedron should be the shape which has the highest random-packing density in the family of tetrahedra, or even among convex bodies. An empirical formula is proposed to describe the rounded corner effect on the packing density, and well explains the density deviation of tetrahedral particles with different roundness ratios. The particles in the simulations are verified to be randomly packed by studying the pair correlation functions, which are consistent with previous results. The spherotetrahedral particle model with the relaxation algorithm is effectively applied in the simulations.